DOKTRIN WAHDAH AL-WUJUD DALAM NASKAH RAMBANG TEGAL - Muhammad Abdullah (LITERASI: Indonesian Journal of Humanities, 2011)
In an ancient mosque in Tegalsari, Tegal regency, Central Java, there are more than twenty manuscripts containing a variety of religious teachings, such as theology, mysticism, jurisprudence, and Arabic language. One of them is a phenomenal classical manuscript namely Rambang manuscripts. The Rambang reveals an esoteric aspect of Islam Martabat Tujuh and Ibnu Arabi’s dogma Wahdah AlWujud, fiqh doctrine, tajalli concept, Allah’s tanzih and tasbih attitude, and classical Islamic theology. This esoteric aspect teaches that God’s existence cannot be recognized by anyone and any power. God can only be recognized after tajalli (appearing Himself) in the universe. This article, by using philological and hermeneutics method, will analyze the influence of Islamic mystical teaching in the Rambang. This article finds that characteristic of Islamic mystic in northern coastal showing two tendencies, Sunni and philosophical Islamic mystic. Furthermore, the Rambang also teaches how to synthesize two concepts, Wahdah AlWujud and Sunni in Islamic tradition. Keywords: teology, tajalli, Wahdah Al-Wujud, esoteric